The characteristics of cognitive general imagery use in curling - Kouali, D.; Westlund Stewart, N.; Hall, C. (Hellenic Journal of Psychology, 2017)
The purpose of this study was to examine the characteristics of cognitive general (CG) imagery use in curling. Participants were 14 curlers, competing at both recreational and competitive levels and predominantly playing the skip position. Three focus groups were conducted, and asked participants questions regarding the characteristics of skips` CG imagery use and how the characteristics differ across various situations, based on Munroe, Giacobbi, Hall, and Weinberg`s (2000) conceptual framework and the revised applied model of deliberate imagery use (Cumming & Williams, 2013). Two themes emerged from the focus groups: characteristics and situations. The results supported the interaction between characteristics and situations of CG imagery use and revealed unique findings regarding the situation and the perspective of CG images.